2018
DOI: 10.1016/j.expneurol.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Continuous tamoxifen delivery improves locomotor recovery 6 h after spinal cord injury by neuronal and glial mechanisms in male rats

Abstract: No treatment is available for patients with spinal cord injury (SCI). Patients often arrive to the hospital hours after SCI suggesting the need of a therapy that can be used on a clinically relevant window. Previous studies showed that Tamoxifen (TAM) treatment 24h after SCI benefits locomotor recovery in female rats. Tamoxifen exerts beneficial effects in male and female rodents but a gap of knowledge exists on: the therapeutic window of TAM, the spatio-temporal mechanisms activated and if this response is se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
0
13
1
2
Order By: Relevance
“…In vivo studies have shown that several estrogenic compounds, such as estradiol, phytoestrogens (genistein), some SERMs and tibolone, decrease reactive astrogliosis and glial scar formation after TBI [123, 169-171, 199-201]. After spinal cord injury, tamoxifen has been shown to first increase astrogliosis at day 2 after injury and then gradually decrease astrogliosis [202]. This suggests that tamoxifen may accelerate the process of astrogliosis, increasing reactive astrocytes in the acute injury phase, where astrocytes may release trophic factors to protect neurons, and decrease reactive astrocytes in the chronic injury phase.…”
Section: Neuroprotective Actions Of Estrogenic Compounds After Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies have shown that several estrogenic compounds, such as estradiol, phytoestrogens (genistein), some SERMs and tibolone, decrease reactive astrogliosis and glial scar formation after TBI [123, 169-171, 199-201]. After spinal cord injury, tamoxifen has been shown to first increase astrogliosis at day 2 after injury and then gradually decrease astrogliosis [202]. This suggests that tamoxifen may accelerate the process of astrogliosis, increasing reactive astrocytes in the acute injury phase, where astrocytes may release trophic factors to protect neurons, and decrease reactive astrocytes in the chronic injury phase.…”
Section: Neuroprotective Actions Of Estrogenic Compounds After Tbimentioning
confidence: 99%
“…The SERM raloxifene increases neurotransmitter receptor binding in brain regions associated with cognition and memory, and enhances the transcription and protein levels of neurotrophic factors such as tropomyosin receptor kinase A (TrkA), BDNF and ChAT in experimental models of TBI in rats [177]. Another SERM, tamoxifen, has been shown to reduce tissue damage and promote functional recovery after traumatic injury of the spinal cord [202]. The phytoestrogen resveratrol reduced neuronal loss in all ipsi- and contralateral hippocampal regions while improving exploratory activity and memory abilities in albino Wistar rats submitted to TBI [178].…”
Section: Neuroprotective Actions Of Estrogenic Compounds After Tbimentioning
confidence: 99%
“…Tamoxifen is a known repressor of astrocyte reactivity acutely after SCI [42,43,55]. Here, we labeled for GFAP to determine if tamoxifen delivered after glial scar formation yielded similar results.…”
Section: Delayed Tamoxifen Treatment Does Not Alter Astrogliosis or Lmentioning
confidence: 99%
“…For example, tamoxifen injected intraperitoneally in adult female rats acutely after toxin-induced demyelination in the brain stimulated NG2 + oligodendrocyte progenitor cell differentiation into oligodendrocytes [OLs] and accelerated the rate of remyelination [35]. Furthermore, 21 days of tamoxifen treatment beginning immediately after SCI reduced inflammation, decreased glial reactivity, promoted cell survival, increased white matter sparing, and enhanced functional recovery in rats and cats [38][39][40][41][42][43]. Interestingly, if tamoxifen treatment was delayed until 42 days after SCI, then hindlimb motor recovery was not changed; the impact of delayed tamoxifen treatment on tissue repair was not assessed [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation